(untitled) (Nepalese Journal of Radiology, 2022)
Introduction: Magnetic resonance imaging is a noninvasive diagnostic modality and provides clinically relevant information to orthopaedic surgeons by detecting and characterizing injuries of cruciate ligaments and meniscus of the knee. MRI is routinely used before arthroscopic examination and surgery. Arthroscopy is considered the reference standard for the diagnosis of injuries of cruciate ligaments and meniscus of the knee and hence the efficacy of MRI needs to be compared with arthroscopic findings. Methods: This was a retrospective observational study at Bheri hospital, Nepalgunj. A total of 114 Patients who were investigated with MRI and managed with arthroscopic procedures for a knee injury, between June 2017 to February 2022, were included in the study.Data analysis was done for determining true positive, true negative, false positive and false negative as per MRI and arthroscopic findings.Sensitivity, specificity, positive predictive value and negative predictive value were calculated based on specific equations. Results: The sensitivity, specificity, positive predictive value, negative predictive value and accuracy of MRI for ACL were 89.65%, 96.42%, 96.29%, 90% & 92.98%, PCL was 96.42%, 100%, 100%, 97.72% & 99.12%, the medial meniscus was 88.46%, 88.70%, 86.79%, 90.10% & 88.59% and lateral meniscus was 84.61%, 94.31%, 81.48%, 95.40% & 92.10% respectively. Conclusions: MRI is an excellent noninvasive modality for imaging the knee and it yields high accuracy in diagnosing injuries of cruciate ligaments and meniscus.